Inhibins Tune the Thymocyte Selection Process by Regulating Thymic Stromal Cell Differentiation - Ebzadrel Carbajal-Franco; Marisol de la Fuente-Granada; Germán R. Alemán-Muench; Eduardo A. García-Zepeda; Gloria Soldevila (Journal of Immunology Research)
Inhibins and Activins are members of the TGF-β superfamily that regulate the differentiation of several cell types. These ligands were initially identified as hormones that regulate the hypothalamus-pituitary-gonadal axis; however, increasing evidence has demonstrated that they are key regulators in the immune system. We have previously demonstrated that Inhibins are the main Activin ligands expressed in the murine thymus and that they regulate thymocyte differentiation, promoting the DN3-DN4 transition and the selection of SP thymocytes. As Inhibins are mainly produced by thymic stromal cells, which also express Activin receptors and Smad proteins, we hypothesized that Inhibins might play a role in stromal cell differentiation and function. Here, we demonstrate that, in the absence of Inhibins, thymic conventional dendritic cells display reduced levels of MHC Class II (MHCII) and CD86. In addition, the ratio between cTECs and mTECs was affected, indicating that mTEC differentiation was favoured and cTEC diminished in the absence of Inhibins. These changes appeared to impact thymocyte selection leading to a decreased selection of CD4SP thymocytes and increased generation of natural regulatory T cells. These findings demonstrate that Inhibins tune the T cell selection process by regulating both thymocyte and stromal cell differentiation.